2015
DOI: 10.1016/j.rfe.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Should I stay, or should I go? – How fund dynamics influence venture capital exit decisions

Abstract: We investigate the determinants of venture capital (VC) exit behavior after the lockup expiry in initial public offerings (IPOs) by considering insights from prospect theory and behavioral finance for the first time. Hereby, the paper concentrates on the under‐researched relationship between fund managers and the limited partners investing in these funds. The results from a proprietary dataset of 292 U.S. VC‐backed IPOs from 1991 to 2008 imply that VC firm characteristics and fund dynamics have a significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 125 publications
(262 reference statements)
0
1
0
1
Order By: Relevance
“…On the other hand, the investment in R&D personnel is also accompanied by extremely high risks due to its disadvantages of a long cycle, high input and immediate effect unavailability. Laura Putre (2016) [8] , Carolin Bock & Mazimilian Schmidt (2015) [9] and others have confirmed through empirical research that technological innovation has a significant promoting effect on corporate performance and it is accompanied by a significant time lag. By constructing a binary logistic model, Ola Lome, Alf Gunnar Heggeseth & Øystein Moen (2016) [3] found that the impact of enterprises' investment in R&D on their earnings has a deferred effect, and its impact lagging for three phases is the most significant one.…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 99%
“…On the other hand, the investment in R&D personnel is also accompanied by extremely high risks due to its disadvantages of a long cycle, high input and immediate effect unavailability. Laura Putre (2016) [8] , Carolin Bock & Mazimilian Schmidt (2015) [9] and others have confirmed through empirical research that technological innovation has a significant promoting effect on corporate performance and it is accompanied by a significant time lag. By constructing a binary logistic model, Ola Lome, Alf Gunnar Heggeseth & Øystein Moen (2016) [3] found that the impact of enterprises' investment in R&D on their earnings has a deferred effect, and its impact lagging for three phases is the most significant one.…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 99%
“…Note-se que o sucesso da indústria depende intimamente da capacidade do VC em realizar ganhos no desinvestimento. Desinvestimentos bem-sucedidos são caracterizados por elevados retornos, o que contribui para o aumento da reputação do VC e desmobiliza recursos que podem ser utilizados em novos investimentos (BOCK; SCHMIDT, 2015).…”
unclassified